Sustainable Oil Palm Production Challenges and Opportunities in Nigeria - C. E. Ikuenobe; M. N. Okoye; Ravindra C. Joshi (Sawit Centre, 2021)
In Nigeria, the oil palm is still very widely exploited in its natural and semi-natural groves, even though the plantation system has grown very popular. While the country has ceased to significantly contribute to the export trade in palm oil from its leading position before 1965, production of the commodity has nonetheless grown significantly since 1974 when the country ceased to export the commodity. Faced with increased domestic demand of palm oil and palm kernel oil for cooking and industrial uses, and a slow growth in production, Nigeria has not been able to produce enough of the commodities to re-enter the export market. The growth of the industry has been largely driven by government policies and initiatives, with little private sector involvement in large-scale industrial estate development. Thus the concerted expansion of oil palm production on an industrial scale as in South East Asia and Colombia has not been replicated in Nigeria. There is enormous potential to expand the industry including a thriving upstream sector given the availability of suitable land and climatic conditions, a large domestic market for palm produce, and an abundance of skilled labour with knowledge of the crop. Recent government policies and fiscal incentives should serve to stimulate investments in the sector and boost competitive production of the crop. This article reviews the various factors which led to the decline in the production and trade of oil palm in Nigeria, and highlights the prospects, potentials, and investment opportunities of the industry in Nigeria.